Microstructural Stability and High-Temperature Oxidation Behavior of Al0.25CoCrCuFeNi High Entropy Alloy - Muhammad, Fadhli; Lestari, Ernyta Mei; Achmad, Tria Laksana; Korda, Akhmad Ardian; Prawara, Budi; Prajitno, Djoko Hadi; Jihad, Bagus Hayatul; Setianto, Muhamad Hananuputra; Basuki, Eddy Agus (National Research and Innovation Agency (BRIN), 2024)
Al0.25CoCrCuFeNi is a high-entropy alloy composed of transition metals, specifically designed for high-temperature applications owing to its favorable mechanical properties, high melting point, and excellent high-temperature resistance. This alloy has been identified as a promising material for space exploration, particularly in the fabrication of combustion chambers and rocket nozzles by the National Aeronautics and Space Agency. Ongoing alloy development involves modifying the elemental composition. This study reduced aluminum content in the equiatomic AlCoCrCuFeNi alloy to Al0.25CoCrCuFeNi, followed by isothermal oxidation treatments at 800, 900, and 1000℃. A series of experiments were conducted to investigate the microstructure stability and oxidation behavior of the Al0.25CoCrCuFeNi alloy. The alloying elements were melted using a single DC electric arc furnace, followed by homogenization at 1100°C for 10 hours in an inert atmosphere. Subsequently, samples were cut into coupons for isothermal oxidation testing at the desired temperatures for 2, 16, 40, and 168 hours. The oxidized samples were characterized using XRD (x-ray diffraction), SEM (scanning electron microscopy) equipped with EDS (energy-dispersive X-ray spectroscopy), optical microscopy, and Vickers hardness testing. The as-homogenized alloy consisted of two constituent phases: an FCC (face-centered cubic) phase in the dendritic region and a copper-rich FCC phase in the inter-dendritic region. The oxides formed during the oxidation process included Al2O3, Cr2O3, Fe3O4, CoO, CuO, NiO, and spinel oxides (Co,Ni,Cu)(Al,Cr,Fe)2O4), with distinct formation mechanisms at each temperature.